Subjective well-being in early adulthood - long-term consequences of inclusive vs. segregated education for students with special educational needs in Germany? - Jonna M. Blanck; Laura Menze; Lena Nusser (European Journal of Special Needs Education, 2024)
We analysed the long-term consequences of inclusive versus segregated educational settings for students with special educational needs in the area of learning (SEN-L, formerly `learning disability”) in Germany. We focused on the consequences of educational settings on subjective well-being (SWB) measured as general life satisfaction five to six years after leaving a mainstream or a special school. We accounted for the selection of students into the different educational settings based on a variety of individual and socio-demographic characteristics. To this end, we conducted entropy balancing and controlled for the current status of not being in education, employment or training (NEET). Young adults who formerly attended segregated special schools reported on average slightly lower levels of life satisfaction. They were also at a much higher risk of being excluded from post-secondary education and the labour market at the age of 20 to 21. However, the differences in life satisfaction were not significant when accounting for systematic differences in individual and socio-demographic characteristics between the two groups. This finding highlights the importance of considering the selection mechanisms underlying educational settings in analyses of outcomes of students with SEN. Their current NEET status did not explain differences in life satisfaction by educational setting.
Keywords: 370; Subjective well-being; life satisfaction; special schools; special educational needs; inclusive education; Germany